EXPERIENCES OF MOTHERS OF CHILDREN WITH INTELLECTUAL DISABILITIES IN SPECIAL SCHOOL SETTINGS IN KARACHI, PAKISTAN: AN EXPLORATORY QUALITATIVE STUDY - Jafri, Farhat; Ali, Shazia; Hussain, Iqra Faraz; Iqbal, Warda; Rehmanzada, Rubina; Mithani, Javeria (Journal of Pakistan Psychiatric Society, 2024)
OBJECTIVES To explore the experiences of mothers of children with intellectual disabilities in special school settings, and to understand the beliefs, views, feelings, specific challenges and lived experiences of raising a child with Intellectual Disability (ID). STUDY DESIGN Exploratory qualitative study. PLACE AND DURATION OF STUDY Four schools for special need students in Karachi, Pakistan from July 2018 to February 2019 (6 months). METHOD Qualitative interviews were conducted with mothers with ages ranging from 18 to 55 years and with only one ID child. A total of 19 mothers agreed and took part in the study. Prior to the start of interviews, written informed consents were taken from all mothers for the interview session, that were conducted in the participants’ local language. The results gathered were analysed by using thematic framework analysis method comprising five steps. RESULTS Five major themes were identified that reflected the experiences of mothers of children with intellectual disabilities: (1) Diagnosis and Reaction to Diagnosis, (2) Maternal Concerns and Future Uncertainties, (3) Effects on Mothers and Coping Strategies, and (4) Perspectives on Support Systems and Recommendations for Improvement. Each theme provides insight into the unique challenges and resilience of mothers navigating their caregiving roles. CONCLUSION The themes identified conclude that mothers’ sufferings are caused by the societal attitude and the adequate provision of health, educational, monetary and moral help. This necessitates the establishment of appropriate and efficient measures, resources and assistance for mothers coping with this stigmatising situation. KEYWORDS intellectual disability, mothers, thematic framework analysis, effective interventions